Four new species of the genus Blaps Fabricius, 1775 from Xizang, China (Coleoptera: Tenebrionidae: Blaptinae: Blaptini) - Zhang, Baoyue; Li, Xinyu; Li, Xiumin (Zootaxa, 2026)
With 214 species, the genus Blaps Fabricius, 1775 is one of the most diverse genera of the tribe Blaptini. In this study, we reconstructed a preliminary phylogenetic tree based on cytochrome c oxidase subunit I (COⅠ) sequences from 41 species, and 38 species belong to the subgenera Ablapsis Reitter, 1887, Blaps Fabricius, 1775 and Nalepa Reitter, 1887 from China. Furthermore, four new species from Xizang, China are described and illustrated: Blaps (Blaps) miranda Li, sp. nov., B. (Ablapsis) tuberculata Li, sp. nov., B. (A.) asperula Li, sp. nov. and B. (A.) gracilis Li, sp. nov. In addition, a key to 18 species of the subgenus Ablapsis is provided. The results of the phylogenetic analyses suggest that the nominotypical subgenus is likely paraphyletic, indicating a need for further phylogenetic studies to clarify the status of the various subgenera.